Comparison of the Effectiveness of Acceptance and Commitment Therapy and Couple Therapy Based on Guttman Model on the Lovemaking Styles of Women Affected by Husband Infidelity - Halajian, Zohreh; Babakhani, Vahideh; Pouyamanesh, Jafar; Jafari, Alireza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to compare the effectiveness of acceptance and commitment-based therapy and couple therapy based on Guttman model on the lovemaking styles of women affected by husband infidelity. Methods The research method was quasi-experimental with pretest-posttest design with a control group and three months of follow-up. The statistical population of the study included all women affected by the infidelity of their husbands who referred to Ramsar Health Center from January 2021 to the end of May 2021. 45 people were selected by convenience sampling who randomly divided into two experimental groups and one control group (15 people in each group). The first and second experimental groups each received 8 sessions of couple therapy based on acceptance and commitment and couple therapy based on Guttman method. The research instrument included the Triangular inventory of love Sterenberg (1986). Data analysis was performed by mixed analysis of variance using SPSS-23 software. Results: In the post-test stage, both methods of intervention improved love styles of intimacy (F=8.57, P<0.001), desire (F=8.55, P<0.001) and commitment (F=8.26, P>0.001) had a significant effect on the effect of women affected by infidelity. In the follow-up phase, two interventions significantly improving lovemaking styles, Also, the results of Bonferroni test showed that couple therapy based on Guttman model is more effective than therapy based on acceptance and commitment on lovemaking styles of women affected by husband infidelity (P<0.01). Conclusion: Based on the findings of the study, couple therapy based on acceptance and commitment and couple therapy based on Guttman method can be used by couples and family therapists to improving lovemaking styles of women affected by infidelity.